Influence of the heat treatment in the electrochemical corrosion of Al-Zn-Mg alloys - Cabot, P. L.; Centellas, F.; Garrido, J. A.; Rogríguez, R. M.; Brillas, E.; Pérez, E.; Benedetti, Assis Vicente [UNESP]; Sumodjo, P. T A (Springer Nature, 1992)
The localized corrosion of Al-(5.03%)Zn-(1.67%)Mg-(0.23%)Cu alloys and high purity Al has been studied using electrochemical techniques, optical microscopy, SEM and EDX. The samples were previously submitted to different heat treatments in which coherent and incoherent MgZn 2 precipitates with different distribution and aggregation degree were produced. The influence of NaCl and Na 2SO 4, dissolved oxygen, immersion time and convection were studied. In NaCl solutions, pitting potentials for the alloys were more negative than for aluminium, indicating an increase in their susceptibility to localized corrosion. Moreover, annealed and cold-rolled alloys presented more negative pitting and repassivation potentials than those submitted to age hardening with direct or interrupted quenching. In annealed and cold-rolled samples, pit nucleation and propagation takes place in the zones where MgZn 2 is accumulated. In the case of the age-hardened alloys, a double pitting behaviour is observed, the first one in the magnesium and zinc enriched regions and the second in the matrix. While the cold water quenched alloy is susceptible to stress corrosion craking, the alloy submitted to the interrupted quenching process is less susceptible to intergranular attack. The sulphate ion shifts the pitting potential of aluminium and the alloys by chloride towards more positive values because it impedes local accumulations of the latter. © 1992 Chapman & Hall.
Keywords: Aluminum Metallography - Precipitation; Corrosion - Electrochemical; Heat Treatment - Effects; Electrochemical Corrosion; Magnesium Zinc Precipitates; Aluminum Zinc Magnesium Alloys